QTL mapping in an interspecific sorghum population uncovers candidate regulators of salinity tolerance - Ashley N. Hostetler (Elsevier, 2021)
Salt stress impedes plant growth and disrupts normal metabolic processes, resulting in decreased biomass and increased leaf senescence. Therefore, the ability of a plant to maintain biomass when exposed to salinity stress is critical for the production of salt tolerant crops. To identify the genetic basis of salt tolerance in an agronomically important grain crop, we used a recombinant inbred line (RIL) population derived from an interspecific cross between domesticated Sorghum bicolor (inbred Tx7000) and a wild relative, Sorghum propinquum. A high-density genetic map was generated from 177 F3:5 RILs and coveres the 10 Sorghum chromosomes with 1991 markers. The genetic map was used to identify 19 total QTL related to plant growth and overall health in optimal and saline conditions. Of these 19 QTL detected, 10 were specific to the salt stress response. The salt-responsive QTL contained numerous genes that have been previously shown to play a role in ionic tolerance, tissue tolerance, and osmotic tolerance, including many aquaporins.